Mobile Phone Based Remote Monitoring System - Liu, Danyi (Auckland University of Technology, 2008)
This thesis investigates embedded databases and graphical interfaces for the MicroBaseJ project. The project aim is the development of an integrated database and GUI user interface for a typical 3G, or 2.5G, mobile phone with Java MIDP2 capability. This includes methods for data acquisition, mobile data and information communication, data management, and remote user interface. Support of phone delivered informatics will require integrated server and networking infrastructure research and development to support effective and timely delivery of data for incorporation in mobile device-based informatics applications. A key research and development (R&D) challenge is to support effective and timely delivery of data for incorporation in mobile device-based informatics applications. Another important aspect of the project is determining how to develop efficient graphics for the small mobile screen. The research investigates and analyses the architecture of a mobile monitoring system. The project developed a generic solution that can be implemented in a number of commercial sectors, such as horticulture, building management and pollution/water management. The developed concept is tested using data relevant to the horticultural area of application. The system also addresses the main issues related to mobile monitoring, including real-time response, data integrity, solution cost, graphical presentation, and persistent storage capabilities of modern mobile devices. Four embedded databases based on J2ME have been investigated. Two of the four have been evaluated and analysed. The Insert function, Sequence Search, and Random Search of Perst List and RMS (Record Management System) databases have been tested. The size of the processed data was limited to 20,000 records when using the wireless toolkit simulator, and 11,000 records when using a mobile phone. Perst Lite reflects good performance and has out-performed RMS in all tests. User interface software such as J2ME Polish for mobile phones has been investigated. Custom J2ME class for graphical interface is developed. This provides the graphical presentation of the data collected from the sensors; including temperature, wind speed, wind direction, moisture, and leaf wetness. The graphical interface, bar charts, and line charts with trace ball for collected data have been designed and implemented. The embedded database performance and project performance have been investigated and analysed. The performances of Perst Lite and RMS are evaluated in terms of the insert, sequence search, and random search functions based on simulation and real devices. The record numbers vary from 1,000 to 20,000. The project performance contains data receiving and storage, and data presentation and configuration. The performance of data storage and configuration can be negated due to the running mode and the response time. Thus, data presenting performance is the key focus in this project. This performance was divided into the categories of initial, data search, data selection, and charting. The initial performance includes the initialisation of the project parameters, and the reaching of the welcome interface. Data search performance refers to the retrieval of the specified data from the embedded database, measured on 48 data points, which only can be presented on the mobile screen from the retrieved data. These four performance types are measured in thousands of record numbers, varying from 1,000 to 18,000 record numbers, with the retrieved data range varying from 1 day to 30 days.
Keywords: Mobile application; Remote control; Mobile phone technology; Cell phone technology; Mobile database applications; Graphic User Interface design; Cellular phones